HIV, visceral leishmaniasis and Parkinsonism combined with diabetes mellitus and hyperuricaemia: A case report - Pandey, Krishna (BioMed Central, 2008)
BACKGROUND: Visceral leishmaniasis is caused by a protozoan parasite, Leishmania donovani and transmitted by the bite of female sandflies. India is endemic for this disease. On the other hand, India contributes to the largest number of cases of HIV as well. CASE PRESENTATION: We hereby report an unusual case presentation of Visceral leishmaniasis/HIV co-infection with additional features of Parkinsonism and hyperuriciemia in an Indian male patient aged about 50 years. CONCLUSION: The increasing incidence of HIV/VL co-infection in India is of utmost importance. The diagnostic and management aspects of these cases are very difficult to handle particularly in an underdeveloped country like India.